Human amplification of secondary earthquake hazards through environmental modifications - Hill, Emma M. (2024)
Anthropogenic climate change and modification of landscapes — such as deforestation, sediment movement, irrigation and sea-level rise — can destabilize natural systems and amplify hazards from earthquake-triggered landslides, liquefaction, tsunami and coastal flooding. In this Perspective, we examine the connections and feedbacks between human environmental modifications and secondary earthquake hazards to identify steps for hazard mitigation. Destabilization of slopes by vegetation removal, agricultural activities, steepening, loading and drainage disruption can amplify landslide hazards. For example, landslides were mainly triggered on deforested slopes after the 2010 and 2021 Haiti earthquakes. Liquefaction hazards are intensified by extensive irrigation and land reclamation, as exemplified by liquefaction causing >15 m of ground displacement in irrigated areas after the 2018 Palu earthquake. Degradation or removal of primary coastal vegetation and coral reefs, destruction of sand dunes, subsidence from groundwater withdrawal, and sea-level rise can increase tsunami inland reach. Restoration of natural coastal habitats could help decrease the maximum inland reach of tsunami, but their effectiveness depends on tsunami size. Sustainable farming practices, such as mixed crop cultivation and drip irrigation, can successfully reduce the saturation of soils and the liquefaction hazard in some situations. Future research should explore the potential of such sustainable practices and nature-based solutions in reducing earthquake-related hazards, in addition to their climate and ecosystem benefits.